Problems of assessing socio-economic damage due to epidemics - G. D. Bryukhanova; V. N. Gorodin; S. M. Romanov; A. N. Redko; D. V. Nosikov; S. V. Grinenko (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. The sudden epidemiological complications that have emerged in the current century have highlighted the serious difficulties on the part of medical services and States in general in responding to epidemiological emergencies of international significance, which required a comprehensive study of the scale of the problem of the negative socio-economic consequences of epidemics for the modern state. The aim of the work was to study the factors that determine the current configuration of medical and social risks in the pre-epidemic period and form the socio-economic significance of epidemics and pandemics in a developed postindustrial society. The results are based on the monitoring, analysis and aggregation of information from specialized national and international industry publications and online resources (medical, socio-economic), as well as materials from peer-reviewed periodicals, on the practical development of author's approaches and assessments of the functioning of the anti-epidemic preparedness system at the international and national levels. Modern factors that aggravate the negative consequences of the pandemic for demography and the state economy in the absence of immunoprophylaxis and specific therapy are identified. Conclusion. The socio-economic significance of epidemiological events in the modern post-industrial society is significantly higher than the predicted level, based on the calculations of the cost of a clinical case of an infectious disease used in the previous century, namely: without including the costs of sanitary and anti-epidemic measures in the foci of the disease, for the deployment of a hospital base; for ensuring a strict anti-epidemic regime of work in medical institutions, for the rehabilitation and restoration of health of persons who have suffered an infectious disease; for the organization of preventive measures in non-medical organizations and enterprises (including information and explanatory work among the population); for the organization of medical care for persons with somatic pathology.